O efeito do método pilates na aptidão funcional e desempenho cognitivo de idosos - Vasconcellos, Silvane Vagner (2020)
Researchers are currently attracting interest in the search for the causes and mechanisms involved in the loss of functional fitness with advancing age and for this reason it is important to create strategies to minimize this loss and maintain or improve health at this stage of life. The aim of this study was to analyze the effects of the Pilates Solo Method (MPS) on the functional fitness and cognitive performance of the elderly. This is an experimental study with pre and post test, involving a pilates group (GP) and a control group (GC). Individuals of both sexes, aged between 60 and 79 who did not practice regular physical exercises were included. Individuals with neurological, cardiovascular, respiratory and orthopedic diseases that prevent Pilates exercises, smoking habits and wheelchair use could not participate in the study. As evaluation instruments were used an evaluation form, Rikli and Jones test, dynamometer test and mini mental state exam. All evaluations were performed before the interventions and redone at the end of this period by the same evaluators. The GP received one-hour MPS classes twice a week for eighteen weeks. After this period, the GC also received the same number of classes. The program SPSS, version 21.0 for Windows was used. For data normality analysis, the Shapiro Wilk test was performed. As it was found that some variables had parametric distribution and others non-parametric, we used the paired t-test and Wilcoxon test in intra-group comparisons and for inter-group comparisons the t-test for independent samples and Mann Whitney test. As a result, a significant difference for the lower limb strength, upper limb strength, lower limb strength, TUG, functional aptitude, right and left arm dynamometer was obtained as a significant difference in the right arm dynamometer and right arm dynamometer. Still, a significant difference was obtained between the groups in lower limb flexibility and functional fitness. It was concluded that after 34 MPS classes, there was an improvement in functional capacity and muscle strength of the elderly.